2012
DOI: 10.4137/ijtr.s10085
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Historic Overview of Clinical Disorders Associated with Tryptophan: The Relevance to Chronic Fatigue Syndrome (CFS) and Fibromyalgia (FM).

Abstract: Last century there was a short burst of interest in the tryptophan related disorders of pellagra and related abnormalities that are usually presented in infancy.1,2 Nutritional physiologists recognized that a severe human dietary deficiency of either tryptophan or the B group vitamins could result in central nervous system (CNS) sequelae such as ataxia, cognitive dysfunction and dysphoria, accompanied by skin hyperpigmentation.3,4 The current paper will focus on the emerging role of tryptophan in chronic fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 65 publications
(136 reference statements)
0
28
0
Order By: Relevance
“…Its levels are reduced because of undernutrition,17 malabsorption,3,32 or any significant illness or injury which upregulates KP catabolism 1…”
Section: Protein Energy Malnutrition (Pem) Niacin and Cofactorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Its levels are reduced because of undernutrition,17 malabsorption,3,32 or any significant illness or injury which upregulates KP catabolism 1…”
Section: Protein Energy Malnutrition (Pem) Niacin and Cofactorsmentioning
confidence: 99%
“…CFS/FM is a complex autoimmune spectrum disorder which is frequently familial 2,3,41,47. The onset is either acute or insidious and has a variable and unpredictable course and outcome.…”
Section: Cfs/fm—the Metabolic Enigmamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is strong evidence of lowering the threshold of pain sensitivity in patients with FM. At the same time, clinical application of diferent methods, such as neurosensory potential testing, revealed that the mechanical allodynia in patients with FM is not restricted to tender points and is prevalent [5].…”
Section: Introductionmentioning
confidence: 99%